Selection criteria and ranking for sustainable hydrogen production options - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
This paper aims to holistically study hydrogen production options essential for a sustainable and carbon-free future. This study also outlines the benefits and challenges of hydrogen production methods to provide sustainable alternatives to fossil fuels by meeting the global energy demand and net-zero targets. In this study, sixteen hydrogen production methods are selected for sustainability investigation based on seven different criteria. The criteria selected in the comparative evaluation cover various dimensions of hydrogen production in terms of economic, technical, environmental, and thermodynamic aspects for better sustainability. The current study results show that steam methane reforming with carbon capture could provide sustainable hydrogen in the near future while the other technologies' maturity levels increase and the costs decrease. In the medium- and long-terms, photonic and thermal-based hydrogen production methods can be the key to sustainable hydrogen production. (c) 2022 The Author(s). Published by Elsevier Ltd on behalf of Hydrogen Energy Publications LLC. This is an open access article under the CC BY license (http://creativecommons.org/ licenses/by/4.0/).
Keywords: Renewable energy; Hydrogen; Hydrogen production; Efficiency; Environmental impact; Sustainability; MUNICIPAL SOLID-WASTE; BIOMASS GASIFICATION; SOCIAL COST; PLASMA GASIFICATION; ENERGY; WATER; METHANE; CYCLE; ELECTROLYSIS; CHALLENGES; Chemistry; Electrochemistry; Energy & Fuels